Design of metastable oxychalcogenide phases by topochemical (de)intercalation of sulfur in La2O2S2 - Sasaki, Shunsuke; Caldes, Maria Teresa; Guillot-Deudon, Catherine; Braems, Isabelle; Steciuk, Gwladys; Palatinus, Lukáš; Gautron, Eric; Frapper, Gilles; Janod, Etienne; Corraze, Benoît; Jobic, Stéphane; Cario, Laurent (Nature communications, 2021)
Designing and synthesising new metastable compounds is a major challenge of today's material science. While exploration of metastable oxides has seen decades-long advancement thanks to the topochemical deintercalation of oxygen as recently spotlighted with the discovery of nickelate superconductor, such unique synthetic pathway has not yet been found for chalcogenide compounds. Here we combine an original soft chemistry approach, structure prediction calculations and advanced electron microscopy techniques to demonstrate the topochemical deintercalation/reintercalation of sulfur in a layered oxychalcogenide leading to the design of novel metastable phases. We demonstrate that La2O2S2 may react with monovalent metals to produce sulfur-deintercalated metastable phases La2O2S1.5 and oA-La2O2S whose lamellar structures were predicted thanks to an evolutionary structure-prediction algorithm. This study paves the way to unexplored topochemistry of mobile chalcogen anions.